International multicentre propensity score-matched analysis comparing robotic versus laparoscopic right posterior sectionectomy. Issue 12 (9th November 2021) - Chiow, Adrian K H; Fuks, David; Choi, Gi-Hong; Syn, Nicholas; Sucandy, Iswanto; Marino, Marco V; Prieto, Mikel; Chong, Charing C; Lee, Jae Hoon; Efanov, Mikhail; Kingham, T Peter; Choi, Sung Hoon; et al.
Abstract: Background: Minimally invasive right posterior sectionectomy (RPS) is a technically challenging procedure. This study was designed to determine outcomes following robotic RPS (R-RPS) and laparoscopic RPS (L-RPS). Methods: An international multicentre retrospective analysis of patients undergoing R-RPS versus those who had purely L-RPS at 21 centres from 2010 to 2019 was performed. Patient demographics, perioperative parameters, and postoperative outcomes were analysed retrospectively from a central database. Propensity score matching (PSM) was performed, with analysis of 1 : 2 and 1 : 1 matched cohorts. Results: Three-hundred and forty patients, including 96 who underwent R-RPS and 244 who had L-RPS, met the study criteria and were included. The median operating time was 295 minutes and there were 25 (7.4 per cent) open conversions. Ninety-seven (28.5 per cent) patients had cirrhosis and 56 (16.5 per cent) patients required blood transfusion. Overall postoperative morbidity rate was 22.1 per cent and major morbidity rate was 6.8 per cent. The median postoperative stay was 6 days. After 1 : 1 matching of 88 R-RPS and L-RPS patients, median (i.q.r.) blood loss (200 (100–400) versus 450 (200–900) ml, respectively; P < 0.001), major blood loss (> 500 ml; P = 0.001), need for intraoperative blood transfusion (10.2 versus 23.9 per cent, respectively; P = 0.014), and open conversion rate (2.3 versus 11.4 per cent, respectively; P = 0.016) were lower in the R-RPS group. Similar results were found in the 1 : 2 matched groups (66 R-RPS versus 132 L-RPS patients). Conclusion: R-RPS and L-RPS can be performed in expert centres with good outcomes in well selected patients. R-RPS was associated with reduced blood loss and lower open conversion rates than L-RPS. Abstract : In this multicentre study, both robotic and laparoscopic right posterior sectionectomies could be performed safely, with excellent outcomes in well selected patients. Robotic surgery was associated with significantly reduced blood loss and lower open conversion rates.